FORCED COLLECTIVATION OF PEASANTS OF UZBEKISTAN AND ITS NEGATIVE CONSEQUENCES - Tishabayeva Lola Arifovna (Web of Journals Publishing, 2024)
The article reveals the dark days of our history — the general collectivization in agriculture and its consequences namely in the years 1930-1933, collectivization was carried out using brutal violence and inclusion of rural population into collective farms with the completion of the kulaks. Opponents of the collectivization were mercilessly sent into exile.
Keywords: collectivization, collective farm, kolhoz, kulak, exile